PENGUKURAN KINERJA RUMAH SAKIT UMUM â€œXâ€ DENGAN METODE SWOT BALANCED SCORECARD - Setiawannie, Yuli; Rahmania, Tiara (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
Performance measurement is an important factor for an organization to control the implementation of the strategy. BSC SWOT method that synergistically can monitor company performance quickly and easily. Hospitals as one type of service company that organizes public health services must have good performance as mandated by Article 28H paragraph (1) of the 1945 Constitution. The purpose of this study is to provide a proposed hospital â€˜Xâ€™ performance measurement model. Based on the results of the study, the strategy direction of the Hospital â€œXâ€ is an aggressive strategy, namely with the power possessed able to take advantage of the opportunities that exist. The performance measurement indicator (KPI) for Hospital â€œXâ€ based on the perspective of the Balanced Scorecard are: 6 financial perspective indicators, 2 customer perspective indicators, 4 internal process perspective indicators, and 5 growth and learning perspective indicators. Based on the total weight of the overall perspective, the highest priority is in the employee productivity indicator of 0.19 and the lowest is the ALOS indicator of 0.014.